2019
DOI: 10.20944/preprints201901.0318.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Intellectual Capital on Firm Value: The Moderating Role of Managerial Ownership

Abstract: Rapidly changing dynamics of globalization and increasing market competition are 11 causing the companies all around the world confronting several new challenges and opportunities.12 To be competitive and successful apart from relative importance of physical resources, companies 13 must adapt modern strategies and policies regarding market flexibility and development. The 14 purpose of this study is to empirically investigate the relationship between intellectual capital and 15 firm value. Furthermore, the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 1 publication
4
11
0
2
Order By: Relevance
“…Human capital, structural capital, capital employed or external capital are referred to as the three basic components of intellectual capital (Ahmed et al , 2019; Kalkan et al , 2014; Nuryaman, 2015). Kalkan et al (2014) affirmed that human capital is the key source of a company’s intangible assets.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Human capital, structural capital, capital employed or external capital are referred to as the three basic components of intellectual capital (Ahmed et al , 2019; Kalkan et al , 2014; Nuryaman, 2015). Kalkan et al (2014) affirmed that human capital is the key source of a company’s intangible assets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research found a positive and significant relationship between intellectual capital and firm value. Ahmed et al (2019) also used the VAIC model to calculate intellectual capital and used Tobin’s Q to measure firm value.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic elements that relate to employees, management, and customers include human and structural capital. There is a growing interest in economic institutions to invest in intellectual capital to reach the achievement of outstanding performance (Ahmed, Khurshid & Yousaf 2019). The results depicted the statistically significant relationship between investing in intellectual capital and achieving outstanding performance within the economic institutions.…”
Section: Measuring Intellectual Capitalmentioning
confidence: 89%
“…There are researchers whose works are dedicated to the problem of establishing the impact of intangibles on the company's MV, in particular, factors such as intellectual capital [Chen et al, 2005;Tseng and Goo, 2005;Maditinos et al, 2011;Khangah et al, 2012;Berzkalne and Zelgalve, 2014;Bchini, 2015;Nimtrakoon, 2015;Nuryaman, 2015;Sardo and Serrasqueiro, 2017;Ahmed et al, 2019;Forte et al, 2019;Mačerinskienė and Survilaitė, 2019], intangible assets [Shahman, 2004;Volkov and Garanina, 2008;Behname et al, 2012;Ramirez and Hachiya, 2012;Shih, 2013;Castro, 2014;Jaara and Elkotayni, 2016;Glova and Mrazkova, 2018;Ocak and Findik, 2019;Vasconcelos et al, 2019], and goodwill [Chauvin and Hirschey, 1994;Shahman, 2004;Li et al, 2010;Cole, 2012]. Only one article related directly to the main focus of our study explores the relationship between customer capital and the company's MV [Taghieh et al, 2013].…”
Section: Literature Reviewmentioning
confidence: 99%